A Case Study on Defining a â€œQuality Algorithmâ€ Based on Correlation between â€˜Existing Quality Model, Different Attributes of Defects & Testsâ€™ - Anurag, Abhishek; Kamatchi, R (International Journal of Engineering and Technology, 2018)
Usage and nature of software systems have changed significantly. Due to this complexity of software systems has also grown exponentially. In these ever-changing requirements and environment in which software system is being used, maintaining quality of software system is very challenging and difficult. If user requirements are not met as expected, itâ€™s called defect. To improve quality, itâ€™s critical to understand and analyze these defects. In this study root cause analysis technique is used to analyze defects and their attributes, root cause of defects and corrective actions of defects. A quality model is designed based on defects, root cause of defects and tests. A quality algorithm is designed in this study depending on existing quality model, defects, tests and their attributes. This quality algorithm is executed on a software system to validate quality model. The results obtained are analyzed to understand the quality of the software system and how itâ€™s different than existing quality model.Â